Penerapan Metode Point Counterpoint untuk Meningkatkan Hasil Belajar PAI Materi Kontrol Diri - Eliza Eliza (MGMP PAI SMP BINTAN, 2022)
This article focuses on the application of the Point Counterpoint learning method to improve Islamic Religious Education learning outcomes in Self-Control material. This study aims to determine the extent to which student learning outcomes increase in the subject of Islamic Religious Education in the subject of Self-Control. To answer this question, this research uses the classroom action research method. Participants in this study were students of class X science high school in the city of Tanjung Pinang which was conducted for two months. The results of the data analysis showed that students who previously did not achieve KKM completeness in learning Islamic Religious Education on Self-Control material experienced a significant increase in learning outcomes after the action was taken, compared to before experiencing the action.